Equine dendritic cells generated with horse serum have enhanced functionality in comparison to dendritic cells generated with fetal bovine serum. Issue 1 (December 2016) - Ziegler, Anja; Everett, Helen; Hamza, Eman; Garbani, Mattia; Gerber, Vinzenz; Marti, Eliane; Steinbach, Falko
Abstract Background Dendritic cells are professional antigen-presenting cells that play an essential role in the initiation and modulation of T cell responses. They have been studied widely for their potential clinical applications, but for clinical use to be successful, alternatives to xenogeneic substances like fetal bovine serum (FBS) in cell culture need to be found. Protocols for the generation of dendritic cells ex vivo from monocytes are well established for several species, including horses. Currently, the gold standard protocol for generating dendritic cells from monocytes across various species relies upon a combination of GM-CSF and IL-4 added to cell culture medium which is supplemented with FBS. The aim of this study was to substitute FBS with heterologous horse serum. For this purpose, equine monocyte-derived dendritic cells (eqMoDC) were generated in the presence of horse serum or FBS and analysed for the effect on morphology, phenotype and immunological properties. Changes in the expression of phenotypic markers (CD14, CD86, CD206) were assessed during dendritic cell maturation by flow cytometry. To obtain a more complete picture of the eqMoDC differentiation and assess possible differences between FBS- and horse serum-driven cultures, a transcriptomic microarray analysis was performed. Lastly, immature eqMoDC were primed with a primary antigen (ovalbumin) or a recall antigen (tetanus toxoid) and, after maturation, were co-cultured with freshly isolated autologous CD5+ T lymphocytes to assess their T cell stimulatory capacity. Results The microarray analysis demonstrated that eqMoDC generated with horse serum were indistinguishable from those generated with FBS. However, eqMoDC incubated with horse serum-supplemented medium exhibited a more characteristic dendritic cell morphology during differentiation from monocytes. A significant increase in cell viability was also observed in eqMoDC cultured with horse serum. Furthermore, eqMoDC generated in the presence of horse serum were found to be superior in their functional T lymphocyte priming capacity and to elicit significantly less non-specific proliferation. Conclusions EqMoDC generated with horse serum-supplemented medium showed improved morphological characteristics, higher cell viability and exhibited a more robust performance in the functional T cell assays. Therefore, horse serum was found to be superior to FBS for generating equine monocyte-derived dendritic cells.